A reconfigurable dual-output buck-boost switched-capacitor converter using adaptive gain and discrete frequency scaling control. (March 2018) - George, Libin; Lehmann, Torsten; Hamilton, Tara Julia
Abstract: This paper presents the design of a dual-output reconfigurable buck-boost switched capacitor converter architecture that can be adapted for applications requiring multiple, distributed on-chip loads. This system uses adaptive gain control and discrete frequency scaling to regulate power delivered. Core-interleaving, an enhanced load regulation scheme, and adaptive switch-sizing control have also been adopted to improve performance. The converter provides a fully-integrated, low-area and fully digital solution. Design and implementation using a standard bulk-CMOS 0.18 µm process provide simulation results showing that the converter has an output voltage range of 1.0–2.2 V, can deliver up to 7.5 mW of power to each load, and is up to 67% efficient, using an active area of only 0.06 mm 2 .